A Deliberate Storying: Considerations of Well-Being among Experienced Canadian Secondary Visual Art Teachers - Atkinson, Amy (Canadian Review of Art Education / Revue canadienne d'éducation artistique, 2025)
This qualitative study explores the lived experiences of three experienced secondary Visual Arts teachers educated in Canada. Following grounded theory, interweaving qualitative in-depth interviews and research creation, the study investigates the well-being of two experienced secondary teachers - one employed at a local school in Montreal and the other at an international school in Shanghai. The insights gleaned from these teacher narratives are then compared to the author's own autoethnographic reflections serving to inform the author’s art-making practice and storying. The findings reveal an imbalance in teacher satisfaction, raising concerns about teacher well-being within the secondary Visual Arts discipline in Canada.